Tree health of mixed species in urban forest of Taman Rimba Alam, Putrajaya, Malaysia - Mat Yaacob, Norbaiah (2017)
Taman Rimba Alam (TRA) is a hidden gem located in Malaysia’s administrative capital, Putrajaya. It was initially conceptualised as an urban forestry showcase that is a combination of a sustainable tropical forest ecosystem and a metropolitan recreational park. This homogenous, man– made forest was created with the intention to reap the same benefits as that of a natural forest especially for communities in urban areas. However, the status of the trees planted in TRA is unknown. Hence, in order to ensure TRA realises its functional capacity to the fullest, the health status of its trees is one major element that must be monitored. This study explores the status of planted trees in TRA, and has two underlying objectives; to assess the health of the trees using physical appearance evaluation and to evaluate the growth performance as well as the mortality rate of the planted trees in the urban forest of TRA, Putrajaya. Subsequent to this, 644 individual trees from various species and sizes were selected and assessed. The tree health inspections were conducted using modified Visual Tree Assessment (VTA) method that was previously established by the International Society of Arboriculture (ISA). In order to obtain tree growth performance, the tree increment rate was determined. This was done by measuring the diameter breast height (DBH) and height on trees that have been planted for nine years. Mortality rate was measured by counting the number of dead trees in an established sample plot (20 x 50m). The assessment of tree health, conducted using the modified VTA method, showed that 92.78% of all the trees were healthy, i.e. they are in good condition and live normally without problems. The remaining 7.22% were found to be problematic; ranging from minor to extremely problematic. The assessment on mortality recorded a low mortality rate with 6.8% of total mortality happening in the nine-year period and 0.8% mortality occurring annually. TRA growth performance yielded good results with average tree mean annual increment (MAI) of DBH 0.98cm (10.07%) annually and MAI of height of 0.73m (9.1%) annually. The tree DBH and height increment recorded a fast increment growth with 90.7% and 81.9% increment rate after nine years. Thus, the high percentage of trees in good condition with low mortality rates, and the success in tree growth performance shows that the health status of planted trees in TRA is classified as “good”. To enhance positive TRA health and to control tree health problems, the TRA planted trees should be continuously and comprehensively monitored.